Valuing Real Estate Investments - Chadha, Harpreet Singh (2009)
Real estate appraisal, property valuation or land valuation is the practice of developing an opinion of the value of real property, usually its Market Value. The need for appraisals arises due to the heterogeneous nature of property as an asset class: no two properties are identical, and all properties differ from each other in their location - which is one of the most important determinants of their value (Wang & Wolverton, 2002). Market value of a parcel of real estate may be defined as the best estimate of the price, at which the property would transact (point of exchange) between a willing buyer and a seller under the prevailing set of market conditions.